Mobile Digital Micro-Integrations and Traditional Music Pedagogy in Timor-Leste - João Mariano Helder de Deus (Journal of Information System and Education Development, 2026)
This study examines the role of music and cultural arts education in fostering child development within the resource-limited context of Timor-Leste’s basic schools (Ensinu Báziku). Implemented through an integrative literature review design, this research synthesizes global pedagogical frameworks and contextualized educational development data from localized developing school systems. The findings indicate that integrating structured rhythmic activities, vocal choir sessions, and traditional cultural arts significantly enhances young learners' cognitive functions, language acquisition, and socio-emotional competencies. Despite severe infrastructural constraints, teacher shortages, and the absolute lack of formal musical instruments in rural sectors, alternative instructional strategies offer highly viable pedagogical solutions. These include the implementation of low-cost traditional percussion instruments and the creative adaptation of mobile digital audio technologies by generalist educators. The study concludes that art-based disciplines should not be marginalized as secondary subjects. Consequently, this paper highlights critical recommendations for educational authorities to integrate structured music pedagogy into the primary curriculum and provide targeted professional training to support holistic child development